1987
DOI: 10.1515/zna-1987-0614
|View full text |Cite
|
Sign up to set email alerts
|

Raman-Studies of the Organic Superconductor β-(BEDT-TTF)2IAuI

Abstract: The resonance Raman spectra of (IAuI)--anions in the organic superconductor β-(BEDTTTF)2IAuI as well as in the electrolyte salt n-Bu4AuI2 are investigated. In contrast to β-(BEDT-TTF)2I3 in the crystals of β-BEDT-TTF)2IAuI at low temperature only one Raman line at 120 cm-1 corresponding to the symmetrical stretching mode of the (IAuI)--anion is observed. No distinct change in the Raman spectra is observed at the superconducting transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…In this context, it is worth mentioning that similar bands have been observed in the Raman spectra of P-(BEDT-TTF),AuI, and were attributed to the symmetric stretching vibration of linear A d , -anions. 21 In the present case the symmetric stretching of Au1,-is observed as a medium-intensity band at 153 em-', in agreement with previous Raman studies of ~-Bu,NALII, . 22 Therefore, the strong Au--1 interaction between adjacent Aul, species in the polymeric polyanion previously proposedz3 appears to have no significant influence on the force constant of the Au-I bond.…”
Section: Spectra Of K-(mdt-ttf)auisupporting
confidence: 92%
“…In this context, it is worth mentioning that similar bands have been observed in the Raman spectra of P-(BEDT-TTF),AuI, and were attributed to the symmetric stretching vibration of linear A d , -anions. 21 In the present case the symmetric stretching of Au1,-is observed as a medium-intensity band at 153 em-', in agreement with previous Raman studies of ~-Bu,NALII, . 22 Therefore, the strong Au--1 interaction between adjacent Aul, species in the polymeric polyanion previously proposedz3 appears to have no significant influence on the force constant of the Au-I bond.…”
Section: Spectra Of K-(mdt-ttf)auisupporting
confidence: 92%
“…1 is less affected by impurities than that reported in Ref. 5. Figure 2 shows the low-temperature polarized Raman spectra of a single crystal of TBA-AuI, obtained by recrystallizing twice from ethyl acetate.…”
Section: Results a N D Discussionmentioning
confidence: 76%
“…As a result, we neglect electronic contributions in our background modelling. For organic charge-transfer salts it has often been reported that the low-temperature specific heat is dominated by Debye and Einstein contributions, resulting from acoustical and low-lying optical phonons [73]. In order to keep the number of fitting parameters small, we considered only one Einstein and one Debye temperature.…”
Section: Specific Heat Measurementsmentioning
confidence: 99%